Inflammatory cell death induced by 5-aminolevulinic acid-photodynamic therapy initiates anticancer immunity - Wang, Lingyan; Chelakkot, Vipin Shankar; Newhook, Nick; Tucker, Stephanie; Hirasawa, Kensuke (Frontiers in Oncology, 2023)
Background Inflammatory cell death is a form of programmed cell death (PCD) that induces inflammatory mediators during the process. The production of inflammatory mediators during cell death is beneficial in standard cancer therapies as it can break the immune silence in cancers and induce anticancer immunity. Photodynamic therapy (PDT) is a cancer therapy with photosensitizer molecules and light sources to destroy cancer cells, which is currently used for treating different types of cancers in clinical settings. In this study, we investigated if PDT using 5-aminolevulinic (5-ALA-PDT) causes inflammatory cell death and, subsequently, increases the immunogenicity of cancer cells. Methods Mouse breast cancer (4T1) and human colon cancer (DLD-1) cells were treated with 5-ALA for 4 hours and then irradiated with a light source. PCD induction was measured by western blot analysis and FACS. Morphological changes were determined by transmission electron microscopy (TEM). BALB/c mice were injected with cell-free media, supernatant of freeze/thaw cells or supernatant of PDT cells intramuscular every week for 4 weeks and then challenged with 4T1 cells at the right hind flank of BALB/c. Tumor growth was monitored for 12 days. Results We found that 5-ALA-PDT induces inflammatory cell death, but not apoptosis, in 4T1 cells and DLD-1 cells in vitro. Moreover, when mice were pretreated with 5-ALA-PDT culture supernatant, the growth of 4T1 tumors was significantly suppressed compared to those pretreated with freeze and thaw (F/T) 4T1 culture supernatant. Conclusion These results indicate that 5-ALA-PDT induces inflammatory cell death which promotes anticancer immunity in vivo.